Geavanceerde diensten: de aantrekkelijkheid van Brussel en lokale uitdagingen - Gilles Van Hamme; Maëlys Waiengnier; David Bassens; Reijer Hendrikse (Brussels Studies, 2020)
Based on an analysis of the dynamics of advanced services in the Brussels economy, which account for more than a third of the total added value in BCR (Brussels-Capital Region), this article looks at the necessity for international attractiveness which accompanies the development of these services. Three reflections are developed in this framework. Firstly, given the international nature of the Brussels economy, the need as well as the possibility to strengthen the international economy linked to advanced services are examined. Next, the competition between the centre and the outskirts in the area of advanced services is examined. Finally, a critical analysis of the social impact of this economy is carried out, highlighting in particular the fact that these activities create few jobs.